Emergency neurosurgery for traumatic brain injury by general surgeons at local hospitals in Sweden: a viable option when time is brain - Francisco Leal-Méndez; Lina Holmberg; Per Enblad; Anders Lewén; Fredrik Linder; Teodor Svedung Wettervik (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Timing of surgical evacuation of mass lesions in traumatic brain injury (TBI) is crucial. However, due to geographical variations, transportation time to the nearest neurosurgical department may be long. To save time, general surgeons at a local hospital may perform the operation, despite more limited experience in neurosurgical techniques. This study aimed to determine whether patient outcomes differed between those who had undergone emergency neurosurgery at local hospitals by general surgeons vs. at university hospitals by neurosurgeons. Methods A nationwide observational study was performed using data from the Swedish Trauma Registry (SweTrau) between 2018 and 2022. A total of 565 TBI patients (local hospitals, n = 21; university hospitals, n = 544) who underwent intracranial hematoma evacuation within 8 h after arrival at the hospital were included. Data on demography, admission variables, traumatic injuries, and outcome (Glasgow Outcome Scale [GOS]) at discharge were evaluated. Favourable vs. unfavourable outcomes were defined as GOS scores of 4–5 vs. 1–3. Results Compared with those treated at university hospitals, patients treated with intracranial hematoma evacuation at local hospitals had lower median Glasgow Coma Scale (GCS) scores (8 vs. 12, p < 0.001), higher rate of acute subdural hematomas (86% vs. 77%, p < 0.001), and lower rate of contusions (14% vs. 53%, p = 0.01). Being operated on at a local hospital was independently associated with higher mortality (p = 0.03) but with a similar rate of favourable outcome (p = 0.74) in multiple logistic regressions after adjustment for demographic and injury-related variables. Conclusions Although a slightly greater proportion of patients who underwent emergency neurosurgery at local hospitals died, there was no difference in the rate of favourable outcome. Thus, in patients with impending brain herniation, when time is of the essence, evacuation of traumatic intracranial bleeding by general surgeons at local hospitals remains a highly viable option.